The radical Isaac : I.L. Peretz and the rise of Jewish socialism - Mahalel, Adi (SUNY series in contemporary Jewish literature and culture., 2023)
Examines the Yiddish-Hebrew writer I. L. Peretz's alignment with the Jewish working-class in Eastern Europe and his devotion to progressive politics.